Relationship between Subjective Oral Health Status and Lifestyle in Elderly People: A Cross-Sectional Study in Japan. (13th May 2013) - Yoshioka, Masami; Hinode, Daisuke; Yokoyama, Masaaki; Fujiwara, Aiichiro; Sakaida, Yasuhiko; Toyoshima, Kenji
Abstract : Objective . The aim of this study was to assess the relationship between subjective oral health status and lifestyle in elderly people living in Japan. Methods . Subjects were 5383 inhabitants of the Kagawa Prefecture, Japan, at the age of 75–100. Records of the number of remaining teeth and the data from self-reported questionnaire were analyzed statistically. Results . Remaining teeth were significantly correlated to "no current smoking, " while not related to other lifestyle. On the other hand, "subjective masticatory ability" defined as a condition allowing chewing all foods well was related to favorable lifestyles. "Subjective masticatory ability" was also related to "not feeling stress, " "no deviated food habit" as well as to other good oral health conditions. A logistic regression analysis for "remaining teeth more than 20" revealed a significant relationship between "no current smoking" (OR = 1.582) and "no alcohol drinking" (OR = 0.851). Regarding "subjective masticatory ability, " all favorable lifestyles analyzed in this study were found to be significant positive factors. Conclusions . "Subjective masticatory ability" seems to be strongly associated with favorable lifestyles. Therefore, it can be suggested that "subjective masticatory ability" might be a good landmark for quality of life of elderly people in addition to the number of remaining teeth.